The association between teachers’ mathematical beliefs, teacher characteristics and student achievements at the junior secondary level of education in Sri Lanka - Wijesundera, Subhashinie; Wijethunga, Kavinda (National Science Foundation: Colombo, 2021)
Mathematics teachers’ beliefs and their effects on student achievements have been studied in other countries for the past many decades. However, there is a limited understanding of mathematics teachers’ beliefs and student achievements in Sri Lanka. Therefore, the current study attempts to explore associations between teachers’ mathematical beliefs, their characteristics and student achievements. To achieve this purpose three main objectives have been set: 1. To identify the association between the beliefs of mathematics teachers and teacher characteristics such as years of experience of teaching, highest educational qualifications in mathematics, and professional qualifications; 2. To assess the relationship between teacher characteristics and student achievements; 3. To identify the relationships between different types of teacher beliefs and student achievements. Data were collected from 50 mathematics teachers who teach Grade Seven classes in the Central Province of Sri Lanka. The sample included one teacher each drawn from a stratified random sample of 50 schools based on school type and ethnicity. The study revealed that teachers with professional qualifications in teaching have better mathematics beliefs than teachers without professional qualifications. The former is more confident in working under stressful conditions and more self-efficacious about teaching specific mathematical competencies. The study further revealed that teacher beliefs related to all three dimensions, considered in the study are not significantly associated with student achievements. Implications of these findings for policy, practice and further research in mathematics education are identified and recommendations for improving mathematics education at the junior secondary level are highlighted.
Keywords: Mathematics teachers; Teacher beliefs; Teacher characteristics; Student achievements; Teacher self-efficacy